1999
DOI: 10.1007/s10107980024a
|View full text |Cite
|
Sign up to set email alerts
|

Intersection theorems on polytopes

Abstract: Intersection theorems on polytopesvan der Laan, G.; Talman, Dolf; Yang, Z. Publication date: 1994 Link to publication Citation for published version (APA):van der Laan, G., Talman, A. J. J., & Yang, Z. (1994). Intersection theorems on polytopes. (CentER Discussion Paper; Vol. 1994-20). Unknown Publisher. General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…If we omit this condition we may still prove that there exists at least one b-balanced n-simplex (not necessarily an odd number of such n-simplexes). Related results were obtained by van der Laan, Talman and Yang [6,7]. Theorem 3.4.…”
Section: Vertices Of F K and With The Vertices Of The Setsupporting
confidence: 52%
“…If we omit this condition we may still prove that there exists at least one b-balanced n-simplex (not necessarily an odd number of such n-simplexes). Related results were obtained by van der Laan, Talman and Yang [6,7]. Theorem 3.4.…”
Section: Vertices Of F K and With The Vertices Of The Setsupporting
confidence: 52%
“…As an application of Theorem 1, we establish a version of a KKM-type intersection result of [14,Theorem 10] which now includes more cardinality information.…”
Section: Resultsmentioning
confidence: 99%
“…The surjectivity of f can also be proved as a consequence of the KKM-type result of [14,Theorem 10] Proof. First, note that because of the Sperner labelling of the triangulation T of P; the map f satisfies f ðFÞ F for any face F of P:…”
Section: A Non-constructive Proof Using Pebble Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be shown that a socially stable game has a non-empty socially stable core. To do so, we formulate an intersection theorem on the unit simplex that generalizes the well-known intersection theorem used by Shapley (1973) (see also Herings, 1997;Ichiishi, 1988;van der Laan et al, 1999). Since socially stable games have a non-empty socially stable core, they also have a non-empty core.…”
Section: Introductionmentioning
confidence: 99%